Restructuring of the intermediate stock in the steel glove production process for the oil and gas sector - Silva, Igor Bernardes da; Pereira, Natália Fernanda Santos; Frossard, Gabriela Correa; Maria, Robert Cruzoaldo (Brazilian Journal of Production Engineering, 2023)
Companies constantly need improvements in the efficiency of their processes, in order to serve their customers with quality products within the agreed delivery time. The efficiency of a company can be related to operational factors, but mainly the management of resources. In this way, management assumes an important function within companies and, when performed inefficiently, it triggers a series of problems that interfere with product quality and delivery to the customer. The present study proposes the restructuring of the intermediate stock of the production process of threaded steel sleeves for the oil and gas sector based on the DMAIC methodology. Through its application, it was possible to eliminate batch mixing problems and loss of traceability that led to process idleness and low productivity. The proposed actions made it possible to standardize the way gloves are stored in the intermediate stock and to reduce the time spent moving material. The results were the increase in the company’s productivity, which reached values ​​5.27% above the production target defined in 2022.